MODEL TINUTUAN TINU KEY UNTUK IBU HAMIL DAN MENYUSUI DI LOKASI RAWAN BENCANA - Grace Langi; Phembriah S Kereh (Jurnal GIZIDO, 2020)
The background of this research, which is based on the phenomenon that occurs related to the pattern of eating habits during the post-disaster in volcano-prone locations in North Sulawesi. Traditional food thinness based on previous research is a nutritious meal required pregnant and nursing mothers, but the initial prescription model of the recipe requires as many as nine basic ingredients of local food that is difficult to fulfill in a state Post-disaster mountain eruptions. The purpose of this research is to produce a model of Tinutuan by observing one local foodstuffs that should not be eliminated and the content of nutritional value similar to the initial prescription. However, modifying it with local foodstuffs is located at the location of the volcano Soputan and Lokon. The research method that has been used is a research development. The results showed that organoleptic tests on ten post-disaster model models of most respondents were more fond of the model containing vegetable. The taste, color, aroma, texture, and appearance of each Tinutuan model remain the same from the initial recipe. Simpulan new prescription model with the use of local food in a mountainous area prone to erupting remains a traditional food that is liked and meets the nutritional needs of pregnant and nursing mothers. It is advisable to create an instant Tinutuan model for nutritional fullness in volcano-prone volcanic locations erupting.